Analysis of infantile fibrosarcoma reveals extensive T‐cell responses within tumors: Implications for immunotherapy. Issue 2 (17th September 2017) - Zhu, Hua; Gu, Song; Yin, Minzhi; Shi, Min; Xin, Chao; Zhu, Jianmin; Wang, Jing; Huang, Siqi; Xie, Chenjie; Ma, Jing; Pan, Ci; Tang, Jingyan; et al.
Abstract: Background: Infantile fibrosarcoma (IFS) is a rare pediatric malignancy with relatively good prognosis, but the risk of progression or recurrence after therapy exists. To understand the immune microenvironment of IFS and determine if immunotherapy is a potential treatment, we analyzed T‐cell responses in IFS tumors. Procedure: IFS tumors were analyzed by immunohistochemistry and multicolor flow cytometry to characterize immune cell infiltration and function. Tumor infiltrating lymphocytes (TILs) were expanded in vitro and evaluated for recognition of autologous tumor cells. Real‐time PCR was applied to evaluate tumor expression of chemokines/cytokines and tumor antigens. Results: Significant infiltration of both CD4 + and CD8 + T cells was found in seven of 10 IFS but rarely found in age‐ and sex‐matched rhabdomyosarcoma tumors. The TILs from recurrent IFS tumors expressed high levels of costimulatory molecules such as CD28, 4‐1BB, and OX40, but little or no coinhibitory molecules such as PD‐1 and CTLA4, Tim3, Lag3, and CD39. Upon activation, large portions of TILs produced IFN‐γ and TNF‐α. Eighteen out of 40 T cell lines generated from surgically removed tumors could recognize autologous tumor cells. Moreover, we found that IFS tumors expressed high levels of T‐cell chemokines such as CXCL10 and CXCL16, and also classic tumor antigens such as CTAG2, GAGE, and NY‐ESO‐1, whose expression could be further enhanced by treatment with epigenetic modulator decitabine. Conclusions: IFS tumors are highly immunogenic and expansion of TILs followed by adoptive cell transfer could be a potential immunotherapy for IFS patients undergoing tumor recurrence.